Pengaruh Penambahan Medium Nutrient Broth (NB) Terhadap Pertumbuhan Bacillus sp. Pada Bioremediasi BOD, COD, Minyak Dan Lemak Di Air Permukaan - Winda Yani Christian S; Aryo Sasmita; Shinta Elystia (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Bioremediation has the potential to be one method in the removal process of organic compounds with initial BOD and COD content of 165.1 mg/L and 5336 mg/L. Utilization of Bacillus sp. in the bioremediation process has a more effective elimination ability where Bacillus sp. have properties such as having a wide range of growth temperatures, forming spores, resistant to antiseptic compounds, are aerobic or facultative anaerobes and do not require relatively expensive growth factors. This study aims to the effect of variations in the medium of growth of Bacillus sp. in port surface water in setting aside the content of BOD, COD, Oil and fat in aerobic processes with contact times of 0, 1, 3, 5 and 7 days. This research was conducted with the Batch Reactor system with a working volume of 8 liters and variations in the medium of Nutrient Broth (NB) bacteria 2 ml, 4 ml, and 8 ml (v / v). The results showed that the highest rate and efficiency of COD removal occurred in the 8 ml bacterial NB medium with 90% removal efficiency. The highest BOD removal efficiency was found in 2 ml bacterial NB medium reactor with removal efficiency of 80% and the highest oil and fat removal efficiency occurred in 8 ml bacterial NB medium with allowance efficiency reaching 88.27%.Keywords: Bioremediation, Port Surface Water, Bacillus sp.